Numerical Simulation of Helically Coiled Closed Loop Pulsating Heat Pipe - Bhagwat Adhikari; Dr. Sanjeev Maharjan (International Journal of Engineering and Management Research, 2019)
This paper addresses the numerical simulation of helically coiled closed loop pulsating heat pipe which is carried in ANSYS Fluent. The values of thermal resistance for constant heat fluxes vs. transient heat fluxes are analyzed. Phase change visualization after the end of simulation is carried out to observe the phenomenon in liquid at its saturation temperature and pressure. Finally, helical heat pipes are found to have thermal resistance less by 2.7K/W, 0.56 K/W, and 0.227 K/W for 8W, 40W and 80W heat inputs than circular pipes. Helical heat pipes are found more efficient than circular heat pipes.